2016
DOI: 10.1111/ijfs.13133
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐acetylcholinesterase, antidiabetic, anti‐inflammatory, antityrosinase and antixanthine oxidase activities of Moroccan propolis

Abstract: Summary Biological properties of Moroccan propolis have been scarcely studied. In the present work, the total phenols and flavonoids from 21 samples of propolis collected in different places of Morocco or 3 supplied in the market were determined, as well as the in vitro capacity for inhibiting the activities of acetylcholinesterase, α‐glucosidase, α‐amylase, lipoxygenase, tyrosinase, xanthine oxidase and hyaluronidase. The results showed that samples 1 (region Fez‐Boulemane, Sefrou city) (IC50 = 0.065, 0.006, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(95 citation statements)
references
References 42 publications
4
81
0
10
Order By: Relevance
“…Inhibition of XO. Xanthine oxidase inhibiting was performed as in El-Guendouz et al 8 An amount of 200 µL of RJ sample solution (5-50 mg/mL), 350 µL of phosphate buffer (pH 7.5, 50 mM), and 50 µL of XO enzyme solution freshly prepared (0.4 units/mL in phosphate buffer, pH 7.5) were mixed and incubated at room temperature for 15 minutes. Then, 330 µL of 0.150 mM xanthine solution were added and the mixture was reincubated for 30 minutes under the same condition.…”
Section: Enzymatic Activitiesmentioning
confidence: 99%
“…Inhibition of XO. Xanthine oxidase inhibiting was performed as in El-Guendouz et al 8 An amount of 200 µL of RJ sample solution (5-50 mg/mL), 350 µL of phosphate buffer (pH 7.5, 50 mM), and 50 µL of XO enzyme solution freshly prepared (0.4 units/mL in phosphate buffer, pH 7.5) were mixed and incubated at room temperature for 15 minutes. Then, 330 µL of 0.150 mM xanthine solution were added and the mixture was reincubated for 30 minutes under the same condition.…”
Section: Enzymatic Activitiesmentioning
confidence: 99%
“…[53] Ethanolic extracts of propolis from several locations in Croatia, analyzed by several methods such as GC/ MS, two-dimensional thin-layer chromatography, HPLC-thin-layer chromatography among others, had relatively high amounts of flavonoids besides the presence of phenolic acids. It was found that the main flavonoids found were pinocembrin (3), pinobanksin (1), pinobanksin-3-O-acetate (4), chrysin (2), quercetin (26), kaempferol (25) pinocembrin-7-methyl ether (27) and galangin (9) (Figure 1), while benzoic (28), ferulic (7), caffeic (5), 3,4-dimethoxycinnamic (29), cinnamic (21) acids were the most abundant phenolic acids. [54][55][56][57][58][59][60][61][62][63][64] However, other authors demonstrated that Croatian propolis contain phenolic acid esters such as CAPE (8), benzyl caffeate (12), benzyl coumarate (30) and cinnamic acid esters.…”
Section: Southern European Coastmentioning
confidence: 99%
“…[110] Northern African Coast Egyptian propolis analyzed by GC/MS was a typical poplar propolis type as reported by [111] but with few differences such as the presence of di-and triterpenes but at very low concentrations. Samples from Upper and East Nile Delta in Egypt were mainly characterized by the presence aliphatic acids (lactic acid, succinic acid, stearic acid, oleic acid, palmitic acid), phenolic acids [benzoic (28), ferulic (7), caffeic (5), 3,4-dime-thoxycinnamic (29), cinnamic (21) and p-coumaric acids (6)] ( Figure 2), flavonoids [pinocembrin chalcone (71), pinocembrin (3) pinobankasin-3-acetate (4)] (Figure 1) and di-and triterpene, in lower amounts, were also detected (e. g., cycloartenol (72), α-amyrin (73), triterpenes of β-amyrin type (74)] (Figure 4). [111,112] Other authors have reported the presence of phenolic acids and di-and triterpenes in Egyptian propolis samples who also reported to find low concentration of aliphatic acids.…”
Section: Levantine Coastmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent approaches for the management of T2D have focused on nutritional interventions using food-derived components (i.e. protein, peptides, phenols and flavonoids) exhibiting antidiabetic activity (El-Guendouz et al, 2016;Loizzo et al, 2016;Zhang et al, 2016). Other studies have investigated the benefit of sugar replacements and/or the use of dietary fibres to reduce the glycaemic index of foods (Foschia et al, 2015;Gao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%